War, capital, and the Dutch state (1588-1795) - Brandon, Pepijn (Historical materialism book series, 2015)
Pepijn Brandon traces the interaction between state and capital in the organisation of warfare in the Dutch Republic from the Dutch Revolt of the sixteenth century to the Batavian Revolution of 1795. Combining deep theoretical insight with a thorough examination of original source material, ranging from the role of the Dutch East- and West-India Companies to the inner workings of the Amsterdam naval shipyard, and from state policy to the role of private intermediaries in military finance, Brandon provides a sweeping new interpretation of the rise and fall of the Dutch Republic as a hegemonic power within the early modern capitalist world-system.